SHOULD MAGISTRATES TAKE DOWN CONFESSIONS? - Llewelyn Gray Curlewis; Willem Gravett (Obiter, 2022)
Section 217(1) of the Criminal Procedure Act 51 of 1977 (the Act) sets forth the requirements for the admissibility of a confession made by any person in relation to the commission of an offence. Section 217(1)(a) provides that where a confession is made to a peace officer who is not a magistrate or a justice of the peace, such a confession must be confirmed or reduced to writing in the presence of a magistrate. Pursuant to section 217(1)(b), where a confession has been made to a magistrate or has been confirmed and reduced to writing in the presence of a magistrate, it is deemed to be admissible in evidence upon mere production (ss (b)(i)); and presumed, unless the contrary is proved, that the accused made the confession freely and voluntarily, while she or he was in her or his sound and sober senses, and without having been unduly influenced in making it (ss (b)(ii)).In S v Zuma (1995 (1) SACR 568 (CC)), the Constitutional Court found that section 217(1)(b)(ii) of the Act violated the right to a fair trial as embodied in section 25(3) of the Constitution of the Republic of South Africa, 1996 (the Constitution). It is a longstanding principle of both English and South African law of evidence that the state bore the burden of proving that any confession on which it wished to rely was freely and voluntarily made. Section 217(1)(b)(ii) of the Act placed on the accused the burden of proving on a balance of probabilities that a confession made to or recorded by a magistrate was not free and voluntary. This section, therefore, created a legal burden of rebuttal on the accused – a so-called “reverse onus”.The court held that the common law rule requiring the state to prove that a confession was made freely and voluntarily, was integral and inherent in the right to remain silent after arrest, the right not to be compelled to make a confession, and the right not to be a compellable witness against oneself. These rights are the necessary reinforcement of the principle that the prosecution must prove the guilt of the accused beyond reasonable doubt. Reversing the burden of proof seriously compromises and undermines these rights. The court thus declared that section 217(1)(b)(ii) of the Act violated the provisions of the Constitution of the Republic of South Africa, 200 of 1993 (the interim Constitution) and was invalid.In the authors’ view, with the Constitutional Court’s decision in Zuma, the principal rationale for sections 217(1)(a) and (b) of the Act seems to have fallen away. After all, the main reason to specifically provide for a confession made to or reduced to writing by a magistrate would be to ease the process of admissibility of such a confession without the need to test its admissibility at a trial-within-a-trial. After Zuma – whether a confession was made to or reduced to writing by a magistrate or not – if the accused contests the admissibility of the confession, the presiding magistrate must hold a trial-within-a-trial in which the state bears the onus of proving the admissibility of the confession on a balance of probabilities.This raises a possibility that did not exist prior to Zuma, namely that a magistrate to whom a confession was made or who reduced it to writing can be called as a witness by the state in a trial-within-a-trial. The authors question whether it is conducive to central tenets of the judicial function – independence and impartiality – for magistrates to take confessions at all, and thus be required to testify in any matter in which accused persons challenge confessions taken down by magistrates.